1990
DOI: 10.1111/j.1432-1033.1990.tb19158.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary structure of human placental 5′‐nucleotidase and identification of the glycolipid anchor in the mature form

Abstract: A cDNA was cloned coding for human placental 5'-nucleotidase. The 3547-bp cDNA contains an open reading frame that encodes a 574-residue polypeptide with a calculated size of 63 375 Da. The NH2-terminal 26 residues comprise a signal peptide, which is followed by the NH,-terminal sequence of the purified protein. Four potential N-linked glycosylation sites are found in the molecule, accounting for a larger mass of the mature form (71 kDa). The predicted structure contains a hydrophobic amino acid sequence at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
107
0
1

Year Published

1992
1992
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(111 citation statements)
references
References 43 publications
(23 reference statements)
3
107
0
1
Order By: Relevance
“…Comparative enzyme assays revealed a higher potential for adenosine formation by way of the latter pathway. Transcripts recognized by a Two metabolic pathways participate in the production of adenosine: cellular transmethylation reactions mouse 5'-NT cRNA probe corresponded in size to the 3.9 kb band identified as 5'-NT mRNA in rat tissues (Misumi et al, 1990). They were detected in the uterus by day 4 of gestation and peaked in the embryo-decidual unit on day 5.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Comparative enzyme assays revealed a higher potential for adenosine formation by way of the latter pathway. Transcripts recognized by a Two metabolic pathways participate in the production of adenosine: cellular transmethylation reactions mouse 5'-NT cRNA probe corresponded in size to the 3.9 kb band identified as 5'-NT mRNA in rat tissues (Misumi et al, 1990). They were detected in the uterus by day 4 of gestation and peaked in the embryo-decidual unit on day 5.…”
Section: Discussionmentioning
confidence: 98%
“…The mouse 5'-NT probe consisted of a 571 bp fragment amplified from poly(A+) RNA from the murine T lymphoma cell line, EL-4, by reverse transcriptase polymerase chain reaction (PCR) (Thompson and Park, unpublished). The primers (forward: 5'-GCGAATTCAGAGAGTGCAACA and reverse 5'-GTGGATCCTTCAACTGCTGGG) were synthesized based upon the published rat 5'-NT cDNA sequence (Misumi et al, 1990). The PCR product was cloned into pBluescript S K + (Stratagene, La Jolla, CAI and sequenced in both directions.…”
Section: Northern Blot Analysismentioning
confidence: 99%
“…General molecular properties EN was first cloned from rat [237], human placenta [238], and the electric ray Torpedo electric organ [239], followed by identification of the cDNA sequence of a considerable variety of mammalian species [202,240]. The human cDNA encodes a precursor of 574 residues that is converted to the mature form of 523 residues after cleavage of the signal peptide and the hydrophobic domain at the C-terminus, which is replaced with the GPI anchor, similar to the enzymes cloned from rat [237] and mouse [204].…”
Section: Ecto-5′-nucleotidase Versus Soluble 5′-nucleotidasesmentioning
confidence: 99%
“…Using sequence information from isolated C-terminal fragments of the mature rat [255], human [238] and bovine [245] enzyme, it was shown that the GPI anchor is linked to the conserved Ser523 residue. The hydrophobic C-terminal extension is cleaved and replaced by GPI.…”
Section: Glycosylationmentioning
confidence: 99%
“…Other ecto-ATPases together with this enzyme form the cascade to finish the action of nucleotides such as ATP and extracellular signaling molecules acting on P2X and P2Y receptors. 5'-nucleotidase is present in basically all tissues and its primary structure has been determined in bovine and rat liver, electric ray brain, mouse kidney and human placenta, showing that the enzyme consists of 548 amino acids with a molecular mass varying between 62 and 74 kDa [90,105,128,135,144]. The protein occurs as a homodimer with interchain disulfide bridges and hydrolyzes a variety of nucleoside 5'-nucleoside monophosphates such as AMP, CMP, UMP, IMP and GMP.…”
Section: '-Nucleotidase: General Characteristicsmentioning
confidence: 99%